2020
DOI: 10.3390/nu12010181
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exposure to High-Fat Diet Induces Long-Term Derepressive Chromatin Marks in the Heart

Abstract: Heart diseases are a leading cause of death. While the link between early exposure to nutritional excess and heart disease risk is clear, the molecular mechanisms involved are poorly understood. In the developmental programming field, increasing evidence is pointing out the critical role of epigenetic mechanisms. Among them, polycomb repressive complex 2 (PRC2) and DNA methylation play a critical role in heart development and pathogenesis. In this context, we aimed at evaluating the role of these epigenetic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Studies from our laboratory found that in the rat prostate gland [ 58 ], neonatal exposure to estradiol/BPA alters the transcriptional program of factors involved in DNA methylation (DNMT3A/B and MBD2/4) and hypomethylation of the promoter of nucleosome binding protein-1 (NSBP1), an early and permanent epigenetic mark of neonatal exposure to estradiol/bisphenol A that persists throughout life. Additionally, maternal high-fat diets in mice have been found to be associated with altered gene expression, chromatin marks, and DNA methylation changes [ 82 , 83 , 84 ] in male and female offspring. However, in our present study, we did not observe any consistent changes in transcripts for the DNA methyl transferases, or for the methyl-CpG-binding domain proteins MBD1, MBD2 , or MBD4 between the various groups in the F1- and F3-generation offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from our laboratory found that in the rat prostate gland [ 58 ], neonatal exposure to estradiol/BPA alters the transcriptional program of factors involved in DNA methylation (DNMT3A/B and MBD2/4) and hypomethylation of the promoter of nucleosome binding protein-1 (NSBP1), an early and permanent epigenetic mark of neonatal exposure to estradiol/bisphenol A that persists throughout life. Additionally, maternal high-fat diets in mice have been found to be associated with altered gene expression, chromatin marks, and DNA methylation changes [ 82 , 83 , 84 ] in male and female offspring. However, in our present study, we did not observe any consistent changes in transcripts for the DNA methyl transferases, or for the methyl-CpG-binding domain proteins MBD1, MBD2 , or MBD4 between the various groups in the F1- and F3-generation offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, rodent cardiac morphogenesis as well as adult cardiac structures are similar to those of human beings [57]. The early period of foetal development is sensitive in rodents, as several studies show blastocyst abnormalities and cardiovascular alterations in undernutrition or HFD models [58,59,65]. Nutritional deficiencies in rodents not only affect the foetal program-ming period but may also induce various pregnancy complications, negatively affecting the foetal environment and possibly triggering the development of CVD in offspring [60].…”
Section: Animal Modelsmentioning
confidence: 99%
“…Data supporting DOHAD: Undernutrition [32][33][34][35][36][37] Overnutrition [38][39][40][41][42] Birth weight [23,[43][44][45] Paternal contribution [1,2,[46][47][48][49][50][51][52][53] ART technique [2,54,55] Easier handling/housing and genetic manipulation [17,56] High sequence conservation with humans [57] Data supporting nutrition and pregnancy complications [58][59][60][61][62][63][64][65] Similarities with human [56,66] Data supporting nutrition and pregnancy complications [67][68][69][70][71][72] Unlimited supply of genetically well-defined material [73] Recapitulate embryonic development [31,…”
Section: Prosmentioning
confidence: 99%
“…Similarly, high fat diet (HFD) alters sperm cells epigenome of sperm cells reprograming, thereby affecting metabolic tissues of offspring throughout two generations [132]. Through such effect, HFD can modulate spermatogenesis via increasing chromatin compaction and affecting the transcription profile of the spermatozoid [133]. Within this context, HFD-induced obesity provides a link with disease related phenotypes in male infertility, i.e.…”
Section: Life Stylementioning
confidence: 99%